SOME STROKE TO THE RECONSTRUCTION OF THE BIOGRAPHY OF THE DAGESTAN ARABIST SCIENTIST AND CAUCASIAN STUDENT M.-S. SAIDOV - Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2023)
The article is devoted to the reconstruction of some facts of the biography of a prominent Dagestan philologist and historian, the founder of the Dagestan school of oriental studies M.-S. Saidov (1902-1985). Having received a brilliant Islamic education, during the years of Soviet power M.-S. Saidov built a brilliant career as a linguist and historian, which is reflected in the numerous autobiographies he wrote between 1948 and 1973. At the same time, additional sources cast doubt on some details of his biography. The purpose of this article is to analyze some sources that show the silence of M.-S. Saidov some facts of his biography. The article uses a comparative analysis of Saidov's autobiographies with various types of ego-documents written by him in Arabic. Reconstruction of some facts of the biography of M.-S. Saidov is also supplemented by alternative sources, including a denunciation of him published in a local newspaper in 1937, as well as the memoirs of his daughter Rabiyat Saidova. Analysis of different types of sources shows that many facts of his biography M.-S. Saidov preferred to hide in his autobiography. This concerns not only some of the facts of his biography, but also his attitude to the events of the period of the Civil War in Dagestan, when his native village of Genichutl was subjected to a punitive action for alleged support of the anti-Soviet rebellion of Najmuddin Gotsinsky (1920-21). Being arrested by the NKVD in the mid-1930s. and miraculously avoiding repression, M.-S. Saidov was forced to carefully conceal certain episodes of his life. At the same time, he wrote about some facts of his biography in brief memoirs in Arabic, as well as reflected his emotions about the events in Genichutla in Arabic verses. The author comes to the conclusion that the Arabic language in M.-S. Saidov served for him as a means of expressing emotions.
Keywords: autobiographies; ego documents; Genichutl; the anti-Soviet revolt of Gotsinsky; Arabic language; poetry; emotions